2010
DOI: 10.1007/s10608-010-9312-4
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and Memory Biases Among Weight Dissatisfied Young Women: Evidence from a Dichotic Listening Paradigm

Abstract: This study investigated attentional and memory biases within the auditory domain among emerging adult women with high levels of fatness and weight concern. A sample of 116 Chinese undergraduate women screened into groups high and low in self-reported weight dissatisfaction engaged in a dichotic listening task. Participants were instructed to shadow (repeat aloud) neutral passages in the attended ear and respond to visual probes, while ignoring distractors (fat, thin, or neutral words) in the unattended ear. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Our findings contradict results reported by Li, Jackson, and Chen (2011), who found that weight dissatisfied women made the most weight-related errors. Though the following results were only of marginal significance, religious, LGBTQ participants had higher EAT scores, indicating weight consciousness.…”
Section: International Journal Of Research Studies In Psychology 95contrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contradict results reported by Li, Jackson, and Chen (2011), who found that weight dissatisfied women made the most weight-related errors. Though the following results were only of marginal significance, religious, LGBTQ participants had higher EAT scores, indicating weight consciousness.…”
Section: International Journal Of Research Studies In Psychology 95contrasting
confidence: 99%
“…In another study by Li, Jackson, and Chen (2011), participants categorized by high and low weight dissatisfaction were presented with a dichotic listening task. While ignoring weight-related and neutral distractors, participants repeated neutral passages as well as attended to visual stimuli.…”
Section: International Journal Of Research Studies In Psychology 89mentioning
confidence: 99%
“…Similarly, the dichotic listening task has also provided evidence in support of an attentional bias among non‐clinical analogue samples. Li, Jackson, and Chen () found that individuals with high weight dissatisfaction made more errors in shadowing the attended passage when fat‐ and thin‐related words were presented in the unattended passage, compared to individuals with low weight dissatisfaction. A limitation of the dichotic listening task is that it uses only auditory stimuli and, therefore, the findings do not provide insight into how people attend to visual stimuli which, as mentioned earlier, may have more real‐world implications.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analytic review [ 10 ], Dobson and Dozois concluded that there was no definitive evidence of attentional biases in non-clinical, at-risk (i.e., body-dissatisfied, dieting, or food-restricting) samples of women, whereas there was clear evidence of attentional biases for weight-related words among women with eating disorder diagnoses. However, several recent studies that used a variety of different methods (e.g., eye-gaze tracking, the dot-probe task, and the dichotic listening task) have found evidence of attentional biases in non-clinical at-risk samples [ 11 , 12 , 26 ].…”
Section: Introductionmentioning
confidence: 99%